Global learning: A post-COVID-19 approach to advance health equity - Dana Marie Parke; Yolanda Ogbolu; Virginia Rowthorn (Global Public Health)
The COVID-19 pandemic has accelerated acceptance of learning from other countries, especially for high-income countries to learn from low- and middle-income countries, a practice known as global learning. COVID-19’s rapid disease transmission underscored how connected the globe is as well as revealed stark health inequities which facilitated looking outside of one’s borders for solutions. The Global Learning for Health Equity (GL4HE) Network, supported by Robert Wood Johnson Foundation, held a 3-part webinar series in December 2021 to understand the current state of global learning and explore how global learning can advance health equity in the post-COVID-19 era. This paper reflects on these cutting-edge discussions about the current state of global learning, drawing upon the highlights, perspectives, and conclusions that emerged from these webinars. The paper also comments on best practices for global learning, including adapting for context, addressing biases, funding considerations, ensuring bidirectional partnerships, community engagement, and adopting a multidisciplinary approach.